Dosis de humus de lombriz y efectos en la producción de biomasa, fijación de CO2 y rendimiento del Maíz Amarillo Duro (zea mays l.) variedad M -28-T - Banda de Shilcayo San Martin-Perú. - Sánchez Sangama, Nísida (2007)
The research was carried out in the experimental fields of the university Nacional De San Martin sect Ahuashiyacu Band Shilcayo Province of San Martin, located at South latitude 6 ° 2T, altitude of 360 m and at a west longitude 76 ° 23 ', has an area of ​​tropical dry forest (bs..T) presents: texture: sandy loam, pH: 4.85, matera organic 3.57 ° .4. block design completely random (OSCA) with 5 treatments and 4 replications. The treatments were 2. 4, 6 TM H. UHA and NPK 160-90-90 and absolute control. ~ Rum treatments that greater plant height and Anura harvest cobs are the T3 (6 TMIHa vermicompost) and 227 .93 cm and 101.00 cm. And the lower results were the TS (absolute control) with 217.95 and 85.78 cm. In grain yield which was obtained higher yield T4 (160-90-90) 3 614. 46 Kg / Ha and treatment that underperformed was the T5 (Witness Absolute) 2 671.81 Kg / Ha. Upon respective economic analysis it is that treatments with high doses of vermicompost reported lost, these treatments & are T3 (6 TMIHa vermicompost) and T2 (4 MT / ha vermicompost) with a loss S / -317.2 and S /. -275.7 Meanwhile T4 (160-90-90) treatment was found to have more gain than all treatments 1os The \ net profit of SJ. in 1. With regard to biomass production, carbon sequestration and CO2 treatments were mejorares results were T3 (6 MT / ha vermicompost) 24 245.3 Kg / Ha biomass 10 815. 4 Kg / Ha carbon and 909.2 Kg / Ha of TOC and T4 (100.9 () .. 90) c: on 24 KglHa biomass 034.1 10 815.4 KglHa carbon and 901.3 Kg / Ha COT.